Integrasi Nilai Spiritual Isra Mi’raj dalam Penguatan Manajemen Ekonomi Komunitas: Studi Kasus Pemberdayaan UMKM di Tangerang Selatan - Tetty Nur Intan Rifia (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the implementation of the spiritual values of Isra Mi’raj in strengthening community-based MSME management in South Tangerang, focusing on MSME actors in East Ciputat District who face challenges in access to capital, financial management, and marketing. A qualitative case study approach was employed over three months (January–March 2025), involving in-depth interviews with 10 MSME actors, field observations, and analysis of supporting documents. The findings reveal three critical insights: First, values of Isra Mi’raj such as sidq (honesty) and ta’awun (collaboration) significantly enhance business resilience by fostering trust and synergy among MSME actors. Second, MSMEs adopting sharia principles (e.g., interest-free transactions, transparency) demonstrated 40% higher sustainability than non-sharia-compliant counterparts. Third, community-based mentoring—including management training and marketing network access—effectively increased annual turnover by 15–25%. Practically, the study recommends an integrated mentoring model involving universities (designing spiritually-aligned curricula), local governments (policy and infrastructure support), and sharia financial institutions (ethical funding access). Theoretically, it enriches community economics literature by affirming that spiritual integration transcends normative discourse, generating measurable economic impacts. These findings establish a framework for inclusive MSME management models that synergize local wisdom, religious values, and sustainable business practices. The research underscores the viability of spiritually grounded approaches in addressing contemporary economic challenges while preserving cultural and ethical integrity.